Are unconscious emotions important in product assessment? How can we access them?. (September 2021) - Thomson, David M.H.; Coates, Toby
Highlights: Hidden influences profoundly important in product-related behaviour. Theory of Constructed Emotion disputes existence of basic emotions. Effectiveness of objective methods in predicting emotion is brought into doubt. Direct questioning vulnerable to over-rationalisation and confabulation. Concept profiling based on non-valance concept terms reaches beyond liking. Abstract: To address the questions posed in the title, we begin by considering the fundamental nature of unconsciousness and emotion. By interpreting this within the framework of a dual-process theory of higher cognition, and generalising emotion into 'mental activity' and unconsciousness into 'no immediate awareness', we conclude that these hidden influences are profoundly important in product-related behaviour. To determine how these influences might be accessed, we explore the Theory of Constructed Emotion, which disputes the fundamental existence of basic emotions along with their supposed neuro-physiological counterparts. Taken at face value this excludes the possibility of using objective methods such as neuroimaging (fMRI), electroencephalography (EEG) and galvanic skin responses (GSR) for predicting emotion. Facial coding is rejected for the same reason. We conclude that direct questioning using procedures such as the EsSense Profile® amongst others, may have some value but they are always vulnerable to over-rationalisation and confabulation. Our preferred approach involves a well-established application of best-worst scaling known as concept profiling. In a new development, this word-based procedure deliberately focuses on non-valence concept terms, identified on the basis of Russell's Circumplex Model of Affect . These, we hold, direct consumers towards hidden influences beyond liking that might otherwise be overlooked. The efficacy of this procedure is demonstrated by comparing two iconic brands, Coke and Pepsi, and what motivates users to choose one brand over the other.